Julgamento moral na contabilidade: estudo sobre o processo educacional de estudantes de graduação e pós-graduação stricto sensu - Marleide Cerqueira de Oliveira (2011)
The social emplacement of an individual represents the environment where they live, which, at the same time, influences the individual and is influenced by them, in a relation of constant exchange. This environment represents the space and time in which experiences are lived, allowing reflection on development of moral behavior. Individuals, in different times in their lives, belong to various social groups; one of these social groups is the academic entourage within a university. The analysis of this context resulted in the investigation of the process of development of moral judgment among students seeking a college degree and students seeking specialization in Science in Accounting stricto sensu. Therefore, the aim of this study was to identify the stages of moral judgment among students seeking a degree of Science in Accounting, during their academic educational process. The basis used for achieving this objective was the Kohlbergs Moral Judgment Theory, which applies six moral judgment stages, divided in three levels: pre-conventional (stages 1 and 2); conventional (stages 3 and 4) and post-conventional (stages 5 and 6), representing the evolution over acquired experiences, including the academic experience. It was noted that stage 3 is predominant in all three analyzed groups: Bachelors, Master Degree and PhD. This stage belongs to the conventional level, which represents the necessity of following rules and social norms, in order to obtain approval of others. In this stage, the moral behavior is the one that pleases, the one that helps or has the approval of others. Although stage 3 is predominant in the researched students, after analyzing the development of moral judgment through p rate, we noticed that college degree seeking students have a higher average than students seeking specialization, in lower Kohlberg moral stages. In the highest stages, students seeking specialization have a higher p rate than college degree seeking students. These findings confirm the theory that sustains that the academic experiences favor the development of moral judgment in individuals.